PENGGORENGAN KERIPIK IKAN NILA DENGAN SISTEM TEKANAN RENDAH (VACUUM FRYING) - Raden Edy Purwanto; Eka Mandayatma; Agus Sujatmiko (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
The purpose of frying process by using oil is to increase calories and drying the fish, as well as to improve the flavor and texture of the food and to create crispy chips. The fish chips are fried in flour with deep fat frying, using cooking oil in large quantities where the processed ingredients are all submerged, so that all materials will get the heat evenly. The size of fish raw is around 3-5 cm.Iif the fish are fried in traditional way, it will change the color and also will cause many missing tail or head so that the shape is no longer interesting. Besides, the original fish chips which are fried without flour are processed under 1 atmosphere. It aims to lower the boiling point below 100 °C to avoid damage to the fish chips so that the shape is good and looks natural. The problem is how to fry tilapia fish which is wholly not destroyed, which looks natural, and has low oil content. The experimental results show the optimal results when fried with low pressure at 90 degree temperature and 90 minute heating time.